Missionary, Reformer, and Old Believer in Revolutionary Russia: Bishop Andrei (Ukhtomskii) (1872–1937). - White, James M. (Journal of Religious History, 2018)
This article examines the life and thought of Andrei (Ukhtomskii), a prominent Orthodox churchman in late imperial and early Soviet Russia. A proponent of ecclesiastical reform, Andrei believed that the Church was unable to instil piety because of an overly close relationship with the state. Basing his opinions on Slavophile philosophy, Andrei campaigned for the restoration of the Russian patriarchate and parish reform that would grant the laity increased autonomy. As a missionary among non‐Russian populations, he rejected linguistic Russification. After 1905, these beliefs led him to clash with the right and Rasputin. After the February Revolution of 1917, the Provisional Government appointed Andrei to a leading position in the Holy Synod. However, during the collapse of the Church's hierarchy in the 1920s, he grew weary of the prevalent inertia and in 1925 attempted to single‐handedly resolve the centuries‐old Old Believer schism. This was rejected by the Moscow Patriarchate, leading Andrei to create his own catacomb church. This article concludes that Andrei should be seen as a church politician undone by the contradictions inherent both in his own position and that of the Church.